Point of View Matters: Seeing, Hearing and Acting in Systemic Practice. Issue 2 (3rd April 2019) - Ray, Wendel A.; Trappeniers, Eric; Hale, David
ABSTRACT: While systemic thinking permeates the fields of couple, family, behavioral, ecological, medical, government, business and political sciences, appreciation of the implications of fundamental presuppositions can be obscured with the passage of time, the emergence and resurgence of alternative approaches. Previously unpublished documents preserved in the Don D. Jackson Archive, will be used as points of reference to discuss elemental presuppositions of the MRI Interactional View from which much of current day systemic practice derive.